射精のコントロール (2021)
会陰組織に電気的作用を及ぼす装置であって、被験者の陰嚢の後面と肛門との間の被験者の会陰表面、に取り付けられるような形状およびサイズを有するハウジングと、会陰組織に電界を供給するように構成されている、ハウジング内の少なくとも２つの電極であって、被験者の陰嚢と肛門との間に全体が配置される、少なくとも２つの電極と、少なくとも２つの電極に電気的に接続されている、ハウジング内のパルス発生器であって、会陰組織内の少なくとも１つの選択されたターゲットに作用するように選択されるパラメータの値を使用して電界を発生させる、パルス発生器と、パルス発生器に電気的に接続されている、ハウジング内の制御回路と、制御回路に電気的に接続されている、ハウジング内の読み書き可能なメモリ回路であって、少なくとも１つの電界パラメータおよび／または少なくとも１つの治療プログラムの通知情報を格納する、読み書き可能なメモリ回路と、を含む、装置。【選択図】 図１Ｂ A device for electrifying perineal tissue, including:a housing shaped and sized to be attached to a perineum surface of a subject between a posterior aspect of the scrotum and the anus of the subject;at least two electrodes in the housing configured to deliver an electric field to a perineal tissue, wherein the electrodes are positioned entirely between the scrotum and the anus;a pulse generator in the housing electrically connected to the at least two electrodes, wherein the pulse generator generates an electric field with parameter values selected to affect at least one selected target within the perineal tissue;a control circuitry in the housing electrically connected to the pulse generator;a readable and writable memory circuit in the housing electrically connected to the control circuitry, wherein the readable and writable memory stores indications of at least one electric field parameter and/or at least one treatment program.